The Portfolio Investment Analysis Using Monte Carlo Simulation in Python: Risk and Return Assessment with Mexican Stocks: Portfolio Investment Analysis Using Monte Carlo Simulation in Python: Risk and Return Assessment with Mexican Stocks. - de la Vega Meneses, José Gerardo (2025)
This study applies Monte Carlo simulation to analyze investment portfolios, focusing on the risk and return of ten selected Mexican stocks from diverse industries. By generating 1,000 random weight combinations, the simulation revealed a wide range of portfolio performance scenarios. Results highlighted the importance of the Sharpe ratio in identifying optimal portfolios, showing that higher returns often come with greater volatility, while stable portfolios provide better risk-return balance. The efficient frontier visualized the relationship between volatility and expected returns. This analysis demonstrates the value of Monte Carlo simulation as a tool for optimizing asset allocation and supporting informed investment decisions.